1991
DOI: 10.1016/1010-7940(91)90142-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic strategy in malignant pleural mesothelioma

Abstract: We retrospectively analysed 301 patients with diffuse malignant pleural mesothelioma (235 male, 66 female; median age 59 years). Prognosis depended significantly on patient age, evidence of pain, loss of weight, tumour cell type, stage, local and distant metastasis, involvement of peritoneum and surgical treatment. The overall median survival rate was 238 days, after extended pleuropneumonectomy 284 days, and after decortication 315 days - significantly better than the prognosis in patients without surgical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…A total of 32 studies met the inclusion criteria (Tables 1-3) and included the following: non-controlled prospective studies with case-series designs or comparative designs not containing similar, concurrent comparison groups, retrospective case-series, or summaries of registry data. Only 12 of the 32 studies reported the type of mesothelioma examined: 11 involved diffuse mesothelioma [16,17,[19][20][21]26,27,30,33,34,38] and one involved localized disease [11].…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 32 studies met the inclusion criteria (Tables 1-3) and included the following: non-controlled prospective studies with case-series designs or comparative designs not containing similar, concurrent comparison groups, retrospective case-series, or summaries of registry data. Only 12 of the 32 studies reported the type of mesothelioma examined: 11 involved diffuse mesothelioma [16,17,[19][20][21]26,27,30,33,34,38] and one involved localized disease [11].…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Lampl and Jakob [22] reported that PL was performed only on patients with early disease (T1a and b), while EPP was performed on patients with more advanced disease (T2 or T3). In the Branscheid et al study [19], EPP was performed with curative intent, and PL was considered palliative. In the study by Aziz et al [23], patients with extensive disease including chest wall invasion and metastases were offered supportive care as were patients who were not fit for surgery.…”
Section: Retrospective Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated thoracocentesis and/or chest tube drainage with drug instillation is a common method used to alle viate the symptoms. However, the average survival peri od of patients with pleural metastasis who received such conservative therapy was 6 months or less [6], The prog nosis of pleural mesothelioma is also unfavorable with or without treatment, the median survival reported in the literature varies from 7 to 16 months [1,3]. Surgery seems to prolong survival [2,7], Complete remission of a pleural mesothelioma has been described in one case with cisplatyl [8], Combination chemotherapy (cyclophosphamide, cisplatyl, mitomycin [9,10] can be used.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients were dis charged from the surgical ward, 3 are still alive 15 months later. Therefore, ITCH appears to be a safe and reliable therapy.Malignant pleural effusion or mesothelioma has ap peared increasingly in the last two decades [1]. Neverthe less, the prognosis is unfavorable with or without treat ment (survival rate from 6 to 16 months).…”
mentioning
confidence: 99%